Varia epigraphica - Schnaible, Elia (Hyperboreus, 2025)
The article provides corrections and new readings of several Greek inscriptions from different parts of the ancient Mediterranean (Aegean islands, Asia Minor, Syria, Sicily) and a hitherto unknown honorific inscription from Megara.